The Impact of LuDiCa Program with a Phonic Approach on the Language and Literacy Skills of Early Childhood Students - Indah Nurmahanani; Neneng Sriwulan (Jurnal Pendidikan Indonesia, 2026)
Many students entering early primary school are still unable to read due to limited literacy activities during the preschool years. This study aims to analyze the impact of the Dialogic Reading for Comprehension (LuDiCa) intervention program, using a phonics-based approach, on the development of young learners’ language and literacy skills. A quasi experimental research design was employed to examine the effectiveness of the dialogic reading program. The research subjects consisted of 250 young children and their parents who participated in the study. Participants were randomly selected from several early childhood education institutions. The instruments used in this study included questionnaires, language and literacy assessments, receptive and expressive vocabulary assessments, taxonomy skills assessments, print awareness assessments, and activity sheets. Data were analyzed using a hierarchical linear model with a two level random intercept. The findings indicate that the phonics-based Dialogic Reading for Comprehension (LuDiCa) program is effective in improving students’ reading and literacy skills. Overall improvements were observed in four aspects of students’ language and literacy abilities: receptive vocabulary, expressive vocabulary, print awareness, and taxonomy skills. In conclusion, the phonics-based dialogic reading literacy intervention program is highly effective in promoting early childhood language and literacy development. The implications of this study suggest that interactive reading activities conducted collaboratively by children and their parents are more effective in supporting language and literacy development.